Commentary: Don't Further Privatize Medicare - David A. Lipschutz (SAGE Publishing, 2019)
The Medicare program is quietly becoming privatized through increasing enrollment in Medicare Advantage (MA) plans, even though MA has not lived up to its promise of delivering better care at lower cost. Policymakers must reverse this trend and ensure parity between traditional Medicare and MA rather than encourage it through legislation that only benefits MA. Furthermore, as discussions of expanding health insurance coverage through Medicare intensify, policymakers should explore what version of Medicare they wish to expand.